HISTORY OF JOURNAL OF THE MALAYSIAN BRANCH OF THE ROYAL ASIATIC SOCIETY (JMBRAS) 1878-1997: AN OVERVIEW - Tiew, Wai Sin (Malaysian Journal of Library and Information Science, 1998)
Traces the historical development of JMBRAS since 1878 when it was first published as JSBRAS in terms of its editorial history, content and coverage, prolific contributors between 1878-1997, visibility of JMBRAS, and publication of its indices.